2020
DOI: 10.17123/atad.777530
|View full text |Cite
|
Sign up to set email alerts
|

Destinasyon Pazarlama Organizasyonlarının Sosyal Medya Performansının Kıyaslanması

Abstract: platformu olan Facebook'tan yararlandıklarını belirtmektedir (Brown 2018). Sosyal medyanın turizm sektörünün gelişimi ve turist davranışı üzerinde giderek artan bir etkiye sahip olması, destinasyonların pazarlama stratejileri içerisinde bu yeni pazarlama platformuna da yer verilmesini gerekli kılmaktadır. Nitekim son yıllarda Destinasyon Pazarlama Organizasyonları'nın (DPO) yüzde 60'tan fazlasının sosyal medya faaliyetlerine bütçe ayırmaya başladığı tespit edilmiştir (Lund, Cohen ve Scarles 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…In a study conducted by Kılıçarslan & Albayrak (2020) to reveal the relationship between the social media performance of destination marketing organizations and the number of visitors to destinations, Facebook, Youtube, Instagram and Twitter performances of destination marketing organizations belonging to the cities that are in the top ten in Europe in terms of visitor numbers were compared. As a result of the study, among the ten most visited destinations in Europe, London was found to be more active on Facebook, Twitter and Instagram compared to other destinations.…”
Section: Related Studiesmentioning
confidence: 99%
“…In a study conducted by Kılıçarslan & Albayrak (2020) to reveal the relationship between the social media performance of destination marketing organizations and the number of visitors to destinations, Facebook, Youtube, Instagram and Twitter performances of destination marketing organizations belonging to the cities that are in the top ten in Europe in terms of visitor numbers were compared. As a result of the study, among the ten most visited destinations in Europe, London was found to be more active on Facebook, Twitter and Instagram compared to other destinations.…”
Section: Related Studiesmentioning
confidence: 99%
“…Instagram Facebook, Instagram and Youtube evaluation form developed by Kılıçarslan and Albayrak (2020) was applied to the section prepared for Instagram while the instagram accounts of the cities were examined in the study. The criteria determined for Instagram consist of the number of followers, the number of followers, the number of posts, likes, comments, the average of likes and the average of comments.…”
Section: Data Collection Process Of the Researchmentioning
confidence: 99%
“…Nitekim araştırmalar, işletmelerin sosyal medya gönderilerine yapılan beğenilerin ve yorumların hacmi ile sosyal medya yönetimindeki başarıları ve müşterilerinin bağlılığı arasında paralel bir ilişki olduğunu ortaya koymaktadır (Uşaklı vd. 2017;Kılıçarslan ve Albayrak 2020).…”
Section: Sonuç Ve öNeri̇lerunclassified
“…2016;Uşaklı vd. 2017;Kılıçarslan ve Albayrak 2020). Öte yandan turizm işletmelerinin sosyal medya kullanımına odaklanan çalışmalar ya sınırlı sayıda işletmeyi örneklemlerine dâhil etmiş (Leung vd.…”
Section: Introductionunclassified